SRSF1-mediated alternative splicing regulates bladder cancer progression and cisplatin sensitivity through HIF1A/BNIP3/mitophagy axis - Qikai Wu; Hao Yu; Huanyou Sun; Jiancheng Lv; Juntao Zhuang; Lingkai Cai; Lingjing Jiang; Yuhan Chen; Yiran Tao; Kexin Bai; Haiwei Yang; Xiao Yang; et al. (Journal of Translational Medicine)
Abstract Background Alternative splicing (AS) is consistently linked to tumor progression. SRSF1, the first identified proto-oncogene in the serine/arginine-rich splicing factor (SRSF) protein family, plays a crucial role. However, the specific functions and potential mechanisms of SRSF1 in advancing bladder cancer (BCa) progression and influencing chemosensitivity remain largely unexplored. Methods The expression of SRSF1 in BCa tissues and cell lines was investigated using quantitative real-time PCR (RT-qPCR) and western blotting. Survival analysis was employed to examine the association between SRSF1 expression and prognosis of BCa. The functions of SRSF1 were evaluated through proliferation assays, migration assays, IC50 determination assays, and tumorigenesis assays in nude mice. Subsequent RNA sequencing validated the relationship between SRSF1 alternative splicing and the mitophagy pathway. Mitochondrial membrane potential (MMP) was assessed using JC-1 staining. Mitophagy and autophagic flux were quantified using transmission electron microscopy and fluorescence imaging. RNA immunoprecipitation, CUT & RUN assays, and luciferase reporter assays were performed to validate the SRSF1/HIF1A/BNIP3 axis. Results High expression of SRSF1 in BCa was significantly associated with poor prognosis. SRSF1 promoted the progression of BCa cells and conferred resistance to cisplatin both in vitro and in vivo. Mechanistically, SRSF1 interacted with pre-HIF1A via the RRM1/RRM2 domain, thereby enhancing the production of the transcription factor HIF1A through the alternative splicing pathway. This interaction subsequently activated the HIF1A/BNIP3 axis, which promoted mitophagy in BCa. Ultimately, this led to further progression of bladder cancer and a decrease in cisplatin sensitivity. Conclusions SRSF1 indicated poor prognosis and promoted the progression and cisplatin resistance of BCa cells through the HIF1A/BNIP3/mitophagy axis. It holds significant potential as a novel biomarker for the diagnosis and treatment of BCa, particularly in chemotherapy.